Language Comprehensibility Analysis of Digital Educational Content on Solar Power Generation for Non-Technical Communities - Ghina Syamilah; Mujibur Rohman; Siti Nuranisa Mulyadi; Teuku Fazrilah Arbaizan; Wiranadi Ramdhani; Mochamad Whilky Rizkyanfi (International Journal of Technology and Education Research, 2026)
The lack of energy literacy among the Indonesian public significantly hinders the adoption of Solar Power Plants, which has only reached 13.09% of the renewable energy mix target by the end of 2023. This study aims to analyze the level of language comprehensibility in digital educational content on PLTS intended for non-technical audiences, using a qualitative descriptive approach through a systematic literature study. Data analysis was conducted using content analysis techniques supported by readability formulas, namely Flesch Reading Ease, Gunning Fog Index, and SMOG. The findings indicate that content produced by official institutions generally falls into the "very difficult" readability category (scores 28–34), while social media content tends to be relatively easier to understand (scores 50–62), although its technical accuracy is often not validated. The use of technical terms such as inverter, maximum power point tracking, and levelized cost of electricity without contextual explanations was found to increase cognitive load among general readers. The study concludes that language simplification and the integration of visual elements are urgently needed to optimize the effectiveness of science communication. These measures have the potential to support the acceleration of energy literacy and contribute to achieving the Net Zero Emissions 2060 target in Indonesia.